2001
DOI: 10.2307/3802916
|View full text |Cite
|
Sign up to set email alerts
|

Use of Acetaminophen for Large-Scale Control of Brown Treesnakes

Abstract: Because the brown treesnake (Boiga irregularis) has virtually extirpated the avifauna on Guam and is a threat to other Pacific islands, the development of alternative and efficient control methods is required. Therefore, we performed a large-scale field experiment to determine whether the acetaminophen baits we developed could be used to reduce population levels of brown treesnakes on Guam. Toxic baits were made by inserting 80 mg of acetaminophen into dead neonatal mice, and these mouse baits were used to tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…The other is aerial bait distribution using biodegradable devices to hang baits in canopy vegetation where they would most likely be encountered by BTS. Similar to trapping, bait stations on plot perimeters with similar spacing as traps have been found to be an efficient and effective strategy for suppressing the snake population inside the plots (Savarie et al, 2001c;. Aerial baiting holds promise as an economical and selective method for reducing BTS populations over large landscapes with little non-target risk .…”
Section: Baiting With Oral Toxicantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other is aerial bait distribution using biodegradable devices to hang baits in canopy vegetation where they would most likely be encountered by BTS. Similar to trapping, bait stations on plot perimeters with similar spacing as traps have been found to be an efficient and effective strategy for suppressing the snake population inside the plots (Savarie et al, 2001c;. Aerial baiting holds promise as an economical and selective method for reducing BTS populations over large landscapes with little non-target risk .…”
Section: Baiting With Oral Toxicantsmentioning
confidence: 99%
“…Commercially available DNM are very effective for delivering acetaminophen to BTS in the field (Savarie et al, 2001c). DNM baits are so well accepted by BTS that bait take is a reliable method for monitoring BTS abundance .…”
Section: Baiting With Oral Toxicantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, toxicants could possibly play a role in controlling Nile monitor lizards and Burmese pythons. Dead neonatal mouse (DNM) baits treated with acetaminophen are effective for reducing brown tree snake populations under field conditions on Guam (Savarie et al 2001). More recently, acetaminophentreated DNMs were found to be lethal to juvenile Nile monitor lizards and Burmese pythons under laboratory conditions (Mauldin and Savarie 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Campbell 2005;Mauldin and Savarie 2010). Building on the successful development of acetaminophen as a toxicant for brown tree snakes (Savarie et al 2001), laboratory trials showed acetaminophen to also be effective for juvenile Nile monitors and Burmese pythons (Mauldin and Savarie 2010).…”
Section: Introductionmentioning
confidence: 99%